PENGARUH LATIHAN SHUTTLE RUN TERHADAP KELINCAHAN ATLET SEPAK TAKRAW PERSERA KUBU KABUPATEN ROKAN HILIR - Efarina Efarina; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: From the observations of researchers in the field at the sepak takraw team, persera, downstream, Rokan Hilir district, there are several weaknesses that appear along with the occurrence of players in training and in sepak takraw matches, namely there are still many technical deficiencies, especially in agility when carrying out movements in carrying out activities. sepak takraw. This can be seen when making passing movements or chasing the ball. So that the sepak takraw team of the rokan downstream district often loses during the match. The purpose of this study was to determine the effect of shuttle run training on the agility of the sepak takraw athletes of the Persera Kubu district of Rokan downstream. The population in this study amounted to 16 people using total sampling, so the sample amounted to 16 people. The instrument in this research is the shuttle run agility test. The data obtained were analyzed using t- test. Based on the t-test, it produces tcount of 3,828 with ttable of 1,764, so H_a is accepted, at an alpha (α) level of 0.05. It can be concluded that there is an effect of shuttle run training on the agility of the sepak takraw athletes of the Persera stronghold of the Rokan Hilir district.dfsdfKey Words: Shuttle run, Agility, Sepak Takraw